Impact of palliative care on psychosocial wellbeing of terminally ill patients in Abeokuta, Ogun state. (2024)
This paper sought to assess the effectiveness of palliative care and investigate the relationship between components of palliative care and the psycho-social well-being of terminally ill patients at the Federal Medical Centre (FMC) in Abeokuta. The study was a descriptive cross- sectional investigation that targeted terminally ill patients at the FMC. Data collection involved an interviewer-administered questionnaire, which included demographic details and assessments using the Modified Palliative Outcome Scale (POS) and the WHO-5 well-being index for evaluating palliative outcomes and psycho-social well-being, respectively. Through Pearson correlation coefficient and multiple logistic regression analysis, three hypotheses were tested. The findings, based on 202 participants, indicated a positive correlation between palliative care outcomes and the psycho-social well-being of patients at FMC Abeokuta (r=.544, P < .01). Further examinations showed that there were positive connections between the medical side and the psychological side of palliative care and how patients were feeling emotionally and socially (r=.395, P < .05) and (r=.296, P< .05) respectively. However, no significant positive correlation was found between social palliative care (social integration and support) and psycho-social well-being. The study recommends that social workers should be employed and be involved in a comprehensive psychological and emotional support interventions which should be integrated into palliative care services in healthcare centres